Mediterranean sponges from shallow subtidal rocky reefs: Cystoseira canopy vs barren grounds. (31st July 2018) - Costa, Gabriele; Bertolino, Marco; Pinna, Stefania; Bonaviri, Chiara; Padiglia, Andrea; Zinni, Matteo; Pronzato, Roberto; Manconi, Renata
Abstract: Porifera richness was investigated in Cystoseira canopies vs barren grounds considering different substrates at 6 areas in the Central-Western Mediterranean Sea. In total 31 sponge taxa were recorded at 2–7 m depth and the sponge community structure and composition were characterized by a notably low richness with 25 taxa in the Cystoseira forest and 15 in the barren area. As for the sponge habitus, the massive sponges were dominant in both facies, whereas encrusting, and cavity dwelling sponges were found in higher numbers in the Cystoseira forest. Results revealed that rocky substrata seem to play a key role in driving the sponge community composition and diversity in both facies. In this work we explore the role of Cystoseira canopy as a suitable facies for sponges. Sponge assemblages were persistent, strongly resilient in space occupation and consequently support stability in both facies. Some species seem to be pre-adapted to live under the sub-optimal conditions of the barren grounds, i.e. the absence of the Cystoseira fronds shelter. This focus on sponge successful eco-etological performances in 'submarine deserts' such as barren areas shows features as shown in a few other sessile benthic invertebrates. Graphical abstract: Image 1 Highlights: Cystoseira canopy and barren grounds are model biotopes to investigate divergences and dynamics in species assemblages. Different sponge assemblages co-occurred at the same biotope at different areas. Species richness of sponges is higher in Cystoseira canopies than in barren grounds. The substrate nature and geographic location of each investigated site contribute to shape species assemblages in the two studied habitats. Some sponge species seem to be pre-adapted to live under the sub-optimal conditions of the barren grounds.